Appraisal Modeling for FSRU Greenfield Energy Projects - Dimitrios Dimitriou; Panagiotis Zeimpekis (Energies, 2022)
Floating storage and regasification units (FSRU) provide a flexible and competitive energy distribution option when it comes to the regasification of liquefied natural gas (LNG). FSRU projects have become more and more popular, attracting the interest of investors, energy authorities, and governments; therefore, the project feasibility in terms of risks and profitability are a major concern. This paper deals with the appraisal of a greenfield LNG infrastructure project, where usually, decision complexity deals with the high number and different expectation of stakeholders, the capital-intensive financing nature, and the business risks in the project life cycle. Conventional wisdom is to provide a coherent, compact, and well-structured appraisal modelling framework, adjusted to FSRU technical, structural, and operational features on one hand; and business risks, long-term life cycle, and investment attractiveness on the other. Appraisal modelling structure and outputs are considered to provide key messages to the decisions involved and interested parties toward the project feasibility and the associated investment risks for the implementation of the FSRU project. The proposed modelling framework was applied to the Alexandroupolis FSRU project, where the first discussion was many years ago, but the existing conditions in the energy market are raising the interest for developing energy distribution facilities globally.